Research of raw material composition effect on the efficiency of the dehydrogenation of paraffins using computer modeling system - Kiseleva S. V. (Химия и химическая технология на иностранном языке Chemistry and Chemical Engineering, in English, 2013)
Заглавие с титульного экрана